2017
DOI: 10.1111/jfpp.13490
|View full text |Cite
|
Sign up to set email alerts
|

Microwave puffing assisted extraction of polysaccharides from Dendrobium devonianum

Abstract: In this study, microwave assisted puffing technology was developed to increase the extraction efficiency of polysaccharides from D. devonianum. Fresh stems of Dendrobium devonianum were processed using microwave puffing technology and the processing conditions were explored and optimized to increase the extraction yield of polysaccharides. The effects of sample length (SL), initial moisture content (IMC), microwave power (MP), and processing time (PT) on quality attributes of the products, in terms of expansio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…It is well known that ethanol precipitation of water extracts allows the separation of high‐molecular‐weight substances, such as polysaccharides and proteoglycans; 23 thus, our results suggest that the puffing process can increase the extraction efficiency of polysaccharides from DO. This is consistent with a previous study by Li et al ., 24 who demonstrated that the extraction yield of polysaccharides from the microwave‐puffed products was increased by 18.9% compared with that from non‐puffed samples.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It is well known that ethanol precipitation of water extracts allows the separation of high‐molecular‐weight substances, such as polysaccharides and proteoglycans; 23 thus, our results suggest that the puffing process can increase the extraction efficiency of polysaccharides from DO. This is consistent with a previous study by Li et al ., 24 who demonstrated that the extraction yield of polysaccharides from the microwave‐puffed products was increased by 18.9% compared with that from non‐puffed samples.…”
Section: Resultssupporting
confidence: 93%
“…The yield of DOOS-HW was slightly lower (42.5%) than that of DO-HW because DOOS-HW was extracted after removing the low-molecular-weight substances by organic solvent pretreatment. When the hot-water extracts were fractionated into crude polysaccharide fractions by the ethanol precipitation method, 7.5DO-CP and 9DO-CP showed higher yields (30.4% and 29.3%, respectively) compared with those of 24 who demonstrated that the extraction yield of polysaccharides from the microwave-puffed products was increased by 18.9% compared with that from non-puffed samples.…”
Section: Resultsmentioning
confidence: 91%
“…The inhibition activity of TFE on lipid peroxidation was detected according to the method of Li with some modifications. 1 mL of TFE solution (20, 40, 60, 80, 100, and 120 μg/mL) was mixed with 0.2 mL of the yolk homogenate (4%, v/v) and 0.2 mL of FeCl 2 solution (25 mmol/L).…”
Section: Materials and Methodsmentioning
confidence: 99%